RACIAL/ETHNIC AND NATIVITY DIFFERENTIALS IN COGNITIVE TRAJECTORIES AMONG OLDER ADULTS IN THE UNITED STATES. (11th November 2018) - Garcia, M; Reyes, A; Downer, B
Abstract: Cognitive decline and dementia represent significant public health challenges that affect the quality of life and independence of older adults. The aging of the U.S. population has coincided with growing racial and ethnic diversity. Previous research documents cognitive disparities by race and ethnicity. However, little is known about variation in cognitive functioning trajectories within minority populations, particularly older Hispanics. Using data from the Health and Retirement Study (1998–2012) we estimate age graded latent growth curve models over a 14-year period to document change in cognitive functioning, based on the Telephone Interview for Cognitive Status (TICS) by gender for White, Black, U.S.-born Hispanic, and foreign-born Hispanic adults 65 years and older. Our results show Black, U.S.-born Hispanic and foreign-born Hispanic women and Black and U.S.-born Hispanic men have lower cognitive functioning at age 65 compared to Whites, independent of socioeconomic and health-related factors. Conversely, years of education and household income attenuate differences in baseline cognitive functioning between foreign-born Hispanic and White men. In addition, we document Blacks and U.S.-born Hispanics, regardless of gender exhibit comparable rates of cognitive decline relative to Whites over the study period. In contrast, foreign-born Hispanic men and women experience a significantly lower decline in cognitive functioning compared to Whites. These findings indicate it is important to consider racial/ethnic and nativity differences in cognitive decline. Understanding minority and immigrant differences in cognitive decline has implications for the development and implementation of culture-appropriate programs to promote healthy brain aging.